MENGGELIATNYA BISNIS DAN INVESTASI PROPERTI DI SURAKARTA - Destina Paningrum (Universitas Sahid Surakarta, 2013)
In this moment , Property Investment be the favouritefor businessman as considered safelyand promising for bright prospects in Surakarta. Moreover, the property segment in Indonesia highly open wide, both for Investment and Business. Shopping center, home propertythat can be a golden opportunity to invest in lucrative property . The demographic layout is located in the city of Surakarta , Central Java province , Indonesia The population of 503.421 inhabitants (2010 ) and the density of 13.636 inhabitants / km2 Where size 44 km2 city that around Karanganyar And Boyolali in northside , Karanganyar And Sukoharjo in next east and west , and Sukoharjo in the south, It's Business Property can be highly profitable , because so many newcomers settled in Surakarta. The Business is growing .In Surakartamalls or shopping center which also adds to the advance of Property in Surakarta.